Development of Ethical Learning Models Based on Toba Batak Culture to Shape Students' Character - Simanullang, Pardomuan; Rajagukguk, Holmes (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to develop and examine the effectiveness of a character education learning model based on Batak Toba cultural values in improving students’ character development and learning outcomes in elementary schools. Methods: This research employed a Research and Development (R&D) approach by integrating the Dick and Carey instructional design model with the Borg and Gall development procedure. The experimental design used a One Group Pretest–Posttest Design, followed by an experimental comparison between experimental and control classes. The research subjects consisted of fourth-grade students from several elementary schools in Humbang Hasundutan Regency, Indonesia. Data were collected through expert validation sheets, student activity observations, learning outcome tests, and character questionnaires. Data analysis was conducted using descriptive and inferential statistics, including normality, homogeneity, and independent t-tests. Results:The results indicate that the developed learning model met the criteria of validity, practicality, and effectiveness. Student learning completeness increased from 61.11% in Trial I to 83.33% in Trial II, and reached 86.11% in Trial III. Statistical testing revealed a significant difference between the experimental and control groups (t = 7.322; p < 0.05), where the experimental group achieved a higher mean score (32.42) compared to the control group (23.39). Furthermore, students’ character responses reached a positive level with an achievement rate of 85.016%. Novelty: The novelty of this study lies in the systematic development of a character education learning model that explicitly integrates Batak Toba cultural values particularly the Dalihan Na Tolu philosophy into a structured five-stage learning syntax: Motivation, Direction, Practice, Demonstration, and Campaign, which has been empirically proven to enhance students’ character formation and learning outcomes.